Village Financial Transparency: Evaluation of the Implementation of the Village Financial System in Improving Accountability in Village Fund Management - Paulus Gundul (Kampus 5 Universitas Negeri Surabaya, 2025)
Transparency and accountability in village financial management are crucial parts in realizing good village governance. This study aims to evaluate the extent to which the implementation of the Village Financial System (Siskeudes) contributes to increasing accountability in the management of village funds, especially in Gonis Tekam Village, Sekadau Hilir District, Sekadau Regency. This system was designed by the Financial and Development Supervisory Agency (BPKP) in collaboration with the Ministry of Home Affairs as an effort to digitize village financial governance so that it is more systematic, measurable, and can be properly supervised.The method used in this study is a qualitative descriptive approach, with data collection techniques through observation, direct interviews with village officials and related stakeholders, as well as documentation studies on financial statements and supporting evidence for the use of Siskeudes. The results of the study show that in general, the implementation of Siskeudes in Gonis Tekam Village has gone quite well and has a positive impact on information disclosure, timeliness of reporting, and regularity of village financial administration. This system also simplifies the process of planning, implementing, and reporting the APBDes, thereby strengthening public trust in the village government.